The Effect Of Nurse's Therapeutic Approach On Reducing The Anxiety Level Of Families Of Critical Patients In The ICU - Sari Arie Lestari B; Rosida Rosida (International Journal of Health Sciences, 2025)
Family of critical patients treated in the Intensive Care Unit Care Units (ICUs) often experience high levels of anxiety due to unstable patient conditions, complex ICU environments, and limited information. One nursing intervention that can be implemented to reduce family anxiety is a therapeutic nurse approach. This study aims to determine the effect of a therapeutic nurse approach on reducing anxiety levels in families of critically ill patients in the ICU. The study used a quantitative design with a pre -experimental one-way approach. group pretest-posttest. The research sample consisted of 40 families of critically ill patients selected using purposive sampling techniques. The research instrument used was the Hamilton questionnaire. Anxiety Rating Scale (HARS). Data analysis was performed using a paired t- test. The results showed a decrease in the anxiety level of families of critically ill patients after being given a therapeutic approach by nurses with a p-value <0.05. The conclusion of this study is that the therapeutic approach by nurses has a significant effect on reducing the anxiety level of families of critically ill patients in the ICU.